Saltlick topography in the Royal Belum Rainforest and species preference - Lazarus, Bryan Andrew (2018)
A saltlick is a natural mineral deposit used by animals in the wild, to supplement dietary nutritional deficiencies. The purpose of this is to ensure that animals, especially herbivores, can obtain the necessary minerals in the diet as salt licks can contain essential nutrients like calcium, magnesium, sodium and zinc. Besides that, when salt licks appear, it serves as a rally point for different wildlife species. In this circumstance, salt licks will be used to identify animal population, animal species, animal food chain, ecosystem and for other biological purposes. Thus, the objective of this study is to determine the relationship between the geographical characteristics of different salt licks in the Royal Belum Rainforest (e.g. rocky areas, low lands or hill areas) and the distinct species of fauna that access the saltlick. The individual location of the salt licks was identified based on the animal trails. Once identified, camera traps were placed in strategic locations directed towards the salt licks to identify which species of animal frequents that salt lick. The results showed that the three different saltlicks differed in terms of size, location, ease of access and the type of vegetation, basically the topography of the saltlicks. The different topography of the saltlicks played a role towards the preference of distinct species of animals the frequent it. Thus, this study suggests that the topography is a crucial factor attraction for wildlife and the different topography of saltlicks influence the diversity or species of wildlife that frequent it.